Co-Teaching and Collaboration: Preservice Teachers’ Knowledge, Attitudes, and Perceived Sense of Efficacy in Teaching Students with Disabilities - Bowlin, Tamara M.; Bell, Sherry Mee; Coleman, Mari Beth; Cihak, David F. (Journal of the American Academy of Special Education Professionals, 2015)
A quasi-experimental design and multiple regression analysis were used to examine responses of 153 preservice general and special education teachers as a function of (a) participation in an introductory special education course and (b) viewing a co-teaching video (Friend, 2005) versus observing an inclusive classroom. Based on responses to pre- and post-measures (30 test-bank items, Mastropieri & Scruggs, 2010; Preservice Inclusion Survey, Shippen, Crites, Houchins, Tamsey, & Simon, 2005; and Teacher’s Sense of Efficacy Scale, Tschannen-Moran, & Woolfolk Hoy, 2001), results showed participants’ knowledge, attitudes, and sense of efficacy increased significantly from pre-to post-course survey (p < 0.001). In addition, participants who viewed the co-teaching video scored significantly higher on self-efficacy (p = 0.04) than those who observed in vivo. However, there were no differences in knowledge or attitudes (p > 0.05) based on video versus observation. Finally, attitudes, but not knowledge, significantly predicted sense of efficacy (R[superscript 2] = 0.21). Implications for teacher preparation programs are discussed.